The relationship between fermentable carbohydrates and post-prandial bowel symptoms in patients with functional bowel disorders - MacIntosh, Alice; Heenan, Phoebe E.; Wright-McNaughton, Morag; Frampton, Chris; Skidmore, Paula; Wall, Catherine L.; Muir, Jane; Talley, Nicholas Joseph; Roy, Nicole Clemence; Gearry, Richard B. (Frontiers in Nutrition, 2023)
Background & Aims: A low fermentable oligosaccharide, disaccharide, monosaccharide and polyols (FODMAP) diet alleviates symptoms of irritable bowel syndrome (IBS). We aimed to investigate the relationship between habitual FODMAP intake and post-prandial bowel symptoms in adults with IBS, functional diarrhoea (FD) or constipation (FD) (functional bowel disorders), and in healthy adults (controls). Methods: 292 participants (173 with functional bowel disorders and 119 controls) completed a food and symptom times diary. Estimated meal portion sizes were entered into the Monash FODMAP Calculator to analyse FODMAP content. Wilcoxon and ANOVA tests were used to investigate the relationship between FODMAP intake and post-prandial bowel symptoms. Results: IBS participants experienced more post-prandial bowel symptoms compared to participants with other functional bowel disorders or controls. Meals associated with abdominal pain contained on average increased excess fructose (0.31g vs 0.18g, p<0.05), sorbitol (0.27g vs 0.10g, p<0.01), and total FODMAP (3.46g vs 2.96g, p<0.05) compared to meals not associated with pain. Abdominal swelling was associated with increased sorbitol (0.33g vs 0.11g, p<0.01), and total FODMAP (3.26g vs 3.02g, p<0.05) consumption. Abdominal bloating was associated with increased galactooligosaccharide consumption (0.18g vs 0.14g, p<0.05). Conclusions: These findings support the role of FODMAP in post-prandial bowel symptom onset, however, the amount and type of FODMAP triggering symptoms vary between individuals. Future research should investigate the relationship between the effect of individual FODMAP consumption on post-prandial bowel symptoms for each subtype, the interaction of FODMAP with differing functional bowel disorders and whether longitudinally symptoms and dietary intake are stable.